Cutaneous Vascular Neoplasms of Uncertain Biological Behavior - Kasey J. McCollum (MDPI AG, 2021)
Neoplasms of uncertain biological behavior present physicians with a genuine conundrum in practice. Cutaneous vascular neoplasms within this category are exceedingly rare, possessing significant gaps and uncertainty in many facets of clinical practice. Firstly, lesions were selected for review based on their categorization as indeterminate behavior, indicating the potential for local recurrence and rarely metastasize. After identification of the target lesions, a comprehensive review of the literature using national databases produced several landmark studies and case series regarding these neoplasms. Limiting the review to only cutaneous limited tumors narrowed the pool of studies; however, quite a large sum of papers remained. Examination of each paper yielded beneficial results on diagnosing, effective treatments, follow-up findings, and prognosis for each indeterminate lesion discussed. Overall, the literature search combined the molecular, histologic, immunohistochemical, surgical strategies to develop an up-to-date and comprehensive framework to guide physicians when encountering such lesions. The tumors reviewed include: kaposiform hemangioendothelioma, endovascular papillary angioendothelioma, pseudomyogenic hemangioendothelioma, retiform hemangioendothelioma, epithelioid hemangioendothelioma, and composite hemangioendothelioma.